Objects of forensic documentary science - V. S. Sezonov (Bulletin of Kharkiv National University of Internal Affairs)
The article is devoted to the scientific analysis of the transformation of the “document” concept as an object of forensic research and to the identification of the main directions of development of forensic documentary science. The methodological basis of the study is the dialectical, formal-logical, formal-legal approaches, and a number of general scientific methods (historical, functional, praxeological). The systematic approach has ensured the comprehensive nature of the study and the unification of its results with a general theoretical conclusion. The scientific novelty lies in the establishment of promising areas for the development of an innovative methodology for conducting forensic document examination in the context of the use of special technical means and the methodology for the use of modern software products.